2022
DOI: 10.3390/nu14153132
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index and Plant-Based Diet with Cognitive Impairment among Older Chinese Adults: A Prospective, Nationwide Cohort Study

Abstract: To examine the association of body mass index (BMI) and a plant-based diet (PBD) with cognitive impairment in older adults, this cohort study used data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), a national, community-based, longitudinal, prospective study in China. Cognitive function was evaluated via the Mini-Mental State Examination (MMSE). Diet was assessed using a simplified food frequency questionnaire (FFQ), and PBD patterns were estimated using the overall plant-based diet index (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…BMI also negatively affects the cognitive performance of fibromyalgia patients [81]. A cohort study from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) supports the positive associations of overweight status with cognitive function in older adults, particularly in those with a higher plant-based diet index [10]. It should be pointed out that other factors, such as physical activity, may also play a role in modifying the association between BMI and cognition in the elderly.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…BMI also negatively affects the cognitive performance of fibromyalgia patients [81]. A cohort study from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) supports the positive associations of overweight status with cognitive function in older adults, particularly in those with a higher plant-based diet index [10]. It should be pointed out that other factors, such as physical activity, may also play a role in modifying the association between BMI and cognition in the elderly.…”
Section: Discussionmentioning
confidence: 85%
“…Maintaining an overweight status (body mass index (BMI) ≥ 25 kg/m 2 ) during midlife was found to increase the risk of cognitive impairment and dementia in later life [9]. Conversely, being overweight in the later stages of life may be associated with a reduced risk of dementia [8,10]. Nevertheless, the precise mechanisms underlying these associations remain unclear [11].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the dietary patterns and characteristics of Chinese older adults, as well as referring to dietary scoring methods proposed by some scholars, we selected a total of 16 types of food as indicators for dietary assessment [ [22] , [23] , [24] ]. These indicators were classified into 3 categories: HPF, which included 8 types of food such as whole grains, vegetable oil, fresh fruits, fresh vegetables, legumes, garlic, nuts, and tea; unhealthy plant-based foods, which consisted of 3 types of food namely refined grains, preserved vegetables and sugar; and animal-based foods, which included 5 types of food namely meat, fish and aquatic products (fish), milk or dairy products, eggs, and animal fat.…”
Section: Methodsmentioning
confidence: 99%
“…Our objective was to assess the relationship between chronic diseases and all-cause mortality and different dietary patterns, using survey data collected from centenarians in China [ 22 ]. Following the common classification methods used in current research, we have categorized 16 types of food intake frequencies into 3 composite dietary patterns [ 23 , 24 ]: plant-based dietary index (PDI), healthy plant-based dietary index (hPDI), and unhealthy plant-based dietary index (uPDI). In addition, we have also calculated the intake scores of the 3 food categories, namely the healthy plant-based foods index (HPF), the unhealthy plant-based foods index (uHPF), and the animal-based foods index (AF), on the basis of the frequency at which different categories of plants are consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all plant-based and anti-inflammatory diets improved pain measurements, whereas not all gluten-free or elimination/restrictive diets showed statistical significance in pain improvement [ 16 ]. The significance of plant-based diets also emerged in a study of cognitive impairment in Chinese adults [ 17 ]. In this longitudinal prospective study, 1077 out of 4792 participants developed cognitive impairment, which showed a reverse J-shaped association with BMI, meaning that overweight and obese participants had a decreased risk, whereas underweight participants had an increased risk of cognitive impairment.…”
mentioning
confidence: 99%